Peran Keterampilan Berbicara dalam Pembelajaran Sains Interaktif pada Materi Biotik, Abiotik, dan Tata Surya di SDI Wolowaru 5: Pengabdian - Bs, Yohana Nono; We’u, Gregorius; Nguru, Melkior; Ga’a, Maria Yosevina Yovita; Loda, Maria Diani Tami; Kaha, Yosep Emanuel Kristian; Botu, Yohanes Ajotur (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Science learning in elementary schools requires an interactive approach to help students understand abstract concepts such as biotic, abiotic, and the solar system. One of the essential elements in interactive learning is speaking skills, particularly students’ ability to communicate through questioning and presenting observations. This study aims to describe the role of speaking skills in interactive science learning at SDI Wolowaru 5. The research employed a descriptive qualitative method with data collected through observation and documentation. The findings show that speaking skills play a significant role in improving students’ understanding of scientific concepts and encouraging their confidence in asking questions during learning activities. In addition, speaking skills help students build self-confidence, participate actively in discussions, and interact more effectively within their groups. Speaking activities also support students in connecting scientific concepts with real-life experiences they encounter daily. Therefore, speaking skills become an important aspect in creating effective, enjoyable, and meaningful interactive science learning in elementary schools.